FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN ASET BIOLOGIS PADA PERUSAHAAN PERKEBUNAN DI INDONESIA DAN MALAYSIA: FACTORS AFFECTING THE DISCLOSURE OF BIOLOGICAL ASSETS IN PLANTATION COMPANIES IN INDONESIA AND MALAYSIA - Oetari Afrilia Ulfa; Nasrizal Nasrizal; Susilatri Susilatri; Pipin Kurnia (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2022)
The purpose of this research is to evaluate and assess the impact of biological asset intensity, company size, KAP type, and profitability on the disclosure of biological assets by plantation companies listed on the Indonesian Stock Exchange and Malaysia Stockbiz between 2016 and 2018. The method used in this study is the method of documentation observation of the sample determined using purposive sampling method. The total samples of this study were 15 samples Indonesian plantation companies and 25 samples Malaysian plantation companies. Hypothesis testing is carried out by using multiple linear regression analysis techniques with the statistical test instrument by using SPSS 25. The results show that biological asset intensity and profitability have an effect on the disclosure of biological assets. Meanwhile, company size and type of KAP have no effect on the disclosure of biological assets in Indonesian plantation companies. Furthermore, in Malaysian plantation companies show that biological asset intensity affects the disclosure of biological assets. Meanwhile, company size, type of KAP and profitability have no effect on disclosure of biological assets.